KAJIAN PERBANDINGAN TABLET TAMBAH DARAH HARIAN DAN MINGGUAN PADA IBU HAMIL TERHADAP KADAR HEMOGLOBIN - Ana Khusnul Faizah; Yagi Dimas Nuryanto; Effendi Rachmat (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2023)
The prevalence of anemia in pregnant women is still high. According to the RISKESDAS 2018, the prevalence of anemia in pregnant women is 48.9%. The impact caused by anemia is low birth weight and bleeding in pregnant women and premature babies. Compliance in consuming daily Iron Folic Acid (IFA) is still a significant obstacle to date, so it is hoped that weekly IFA supplementation can improve compliance in pregnant women. This study aimed to determine the effect of daily versus weekly use of IFA in pregnant women on hemoglobin levels. The method used is a literature review. The search strategy used uses a database (Pubmed, Google Scholar, and Science Direct) with the keywords Pregnancy (Population), Iron supplementation (Intervention), Daily and Weekly (Comparison), and Hemoglobin (Outcome). The study obtained nine journals as study material. The nine journals showed that daily iron supplementation in non-anemic pregnant women gave better results in terms of adherence, and hemoglobin levels showed an increase that was not significantly different from daily. Weekly iron supplementation can be ensured in non-anemic pregnant women because it can increase hemoglobin levels to prevent anemia in pregnant women.